2021
DOI: 10.1515/med-2021-0289
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-19 pandemic on stress levels of urologic patients

Abstract: Introduction Several studies have shown the consequences of COVID-19 pandemic on perceived stress of different populations, but none of them analyzed urological patients who underwent elective surgery. Methods We enrolled prospectively patients who underwent elective surgery between March and October 2020. A survey on COVID-19 and the 4-item Perceived Stress Scale (PPS-4) questionnaire were administered at hospital admission.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Furthermore, the perceived stress levels of oncology patients who underwent elective surgery during the pandemic were higher than those without an oncologic disease. 31 Al Rahimi et al 32 found that during the pandemic, fear and health anxiety were more common in patients taking immunosuppressants or those with chronic diseases (Crohn's disease, cardiovascular diseases). Kapıkıran et al 33 revealed that patients' surgical fear varied according to the presence of chronic disease in patients undergoing abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the perceived stress levels of oncology patients who underwent elective surgery during the pandemic were higher than those without an oncologic disease. 31 Al Rahimi et al 32 found that during the pandemic, fear and health anxiety were more common in patients taking immunosuppressants or those with chronic diseases (Crohn's disease, cardiovascular diseases). Kapıkıran et al 33 revealed that patients' surgical fear varied according to the presence of chronic disease in patients undergoing abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with patients who underwent elective urological surgery found that those who had fear of Coronavirus infection had higher levels of perceived stress in the preoperative period. 31 Another study shows that fear of viruses can affect the decision-making process of patients and may have negative consequences on patient outcomes. 42 The study results reveal that the fear of surgery is related to the fear of Coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…PLND was performed in all patients and the extended template was applied when the risk of lymph node involvement was >5% according to the memorial Sloan–Kettering nomogram, and since 2019 when the risk was >7% according to Gandaglia's nomogram ( 5 , 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, EAU guidelines recommend that extended pelvic lymph node dissection (ePLND) to be performed according to validated nomograms; patients with lymph node involvement risk constitute >5% according to Briganti's or Memorial Sloan Kettering nomogram, or those with risk >7% according to Gandaglia's nomogram shall undergo ePLND. Although ePLND remains the most accurate method for staging PCa confined to the pelvis, its therapeutic benefit is still unclear (5)(6)(7). ePLND provides better pathological staging than standard PLND, facilitating subsequent multimodality treatments, while no difference in oncological outcomes has been demonstrated (4, 8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, there was relevant mental stress and uncertainty about the COVID-19 pandemic among urologists [32][33][34]. The psychological discomfort and the intense fear of infection were significant burdens [29].…”
Section: Plos Onementioning
confidence: 99%